2020
DOI: 10.3390/ijerph17165864
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Practices and Adolescent Obesity in Secondary School Learners at Disadvantaged Schools in South Africa: Urban–Rural and Gender Differences

Abstract: South Africa has a high prevalence of obesity in black female adolescents and a paucity of knowledge regarding contributing dietary practices. The aim of this study was to assess the dietary practices and weight status of male and female adolescents at secondary schools in the Eastern Cape province in urban and rural areas. Sixteen schools and grade 8–12 learners (N = 1360) were randomly selected from three health districts comprising poor disadvantaged communities. A short unquantified food frequency question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
4
14
1
Order By: Relevance
“…Results showed that adolescents residing in urban settings had higher chances of becoming obese than their rural counterparts 24 . These results corroborate with other African studies which showed an association between urban settings and high BMI 42,43 . However, contrary to this finding, Ghana reported higher rates of obesity in rural settings compared to urban settings 44 .…”
Section: Environmental Factorssupporting
confidence: 93%
“…Results showed that adolescents residing in urban settings had higher chances of becoming obese than their rural counterparts 24 . These results corroborate with other African studies which showed an association between urban settings and high BMI 42,43 . However, contrary to this finding, Ghana reported higher rates of obesity in rural settings compared to urban settings 44 .…”
Section: Environmental Factorssupporting
confidence: 93%
“…Almost 17% of children are with obesity in the USA, whereas one out of three children is overweight/obese in Europe. Similar results are shown in Africa, where obesity in female adolescents (36.1%) is more prevalent than in males (3,4). These metabolic changes are mainly attributed to sedentary lifestyle and unhealthy dietary pattern (e.g., easy access to fast-food and sugar-sweetened beverages) (5).…”
Section: Introductionsupporting
confidence: 69%
“…In addition to the “local traditional” pattern, the other three dietary patterns have a higher adherence score with the urban group, which showed that rural residents were more inclined towards the local traditional diet. Due to the convenience of infrastructure and transportation, people living in urban areas have more access to more diverse foods [ 33 ]. Moreover, with higher per-capita revenue, urban families are able to buy more varieties of food and consume more food overall [ 7 ].…”
Section: Discussionmentioning
confidence: 99%